The Dikyasa Traffic Unit's Efforts to Prevent Traffic Accidents Stand Out - Lobat, Meiselin (Advances in Police Science Research Journal, 2024)
This research is motivated by a prominent traffic accident (Lakajol) which experienced fluctuations in the last three years 2017-2019 in the Cipali Toll, the Majalengka police area which can be said to be high is due to the lack of awareness of road users and other factors such as the absence of permanent road median, limited rest area, lack of signs and many vehicles carrying loads more than the capacity limit. So that research is conducted to find out traffic accidents at the Cipali Toll Road, efforts from Dikyasa Unit in preventing Lakajol, and factors what influences the performance of Dikyasa Unit in preventing Lakajol. The theories used by the writer are Management theory from George R. Terry, and Achieve Theory from Wibowo and the concept of effort, concept of dikyasa, concept of prevention, concept of traffic and concept of lakajol. This research uses a qualitative approach, uses descriptive analysis research methods and uses data collection techniques in interviews, observations and document studies. The results of the study found that the implementation of prevention has not gone well marked by the high level of supporting factors in these activities is the number of vehicles exhausted out of control and out of line A to line B or vice versa there is cooperation with relevant agencies but many activities that have not been realized lack of rest area also the findings of the authors in the field. the inhibiting factor in the activity is the lack of personnel in the unit other than that related agencies that have direct responsibility there is still no information related to the construction of the road median, signs and other matters that are related to the prevention of Lakajol. The writer concludes that Lakajol has fluctuated, there are patrols and appeals made at Rest Are Delayed (ODOL). The number of Dikyasa unit personnel is still lacking and the number of rest areas is also still lacking. The author suggests that Patrol be increased again 2-4 times a month, increase supervision, increase personnel, install a road median, and add rest areas so that they are coordinated with relevant agencies and increase cooperation with related agencies.